2020
DOI: 10.1111/edt.12599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of conditioned medium from placenta‐derived mesenchymal stem cells as a storage medium for avulsed teeth: An in vitro study

Abstract: Background/Aim: The viability of periodontal ligament cells on the root surface is a major factor that influences the healing of replanted teeth. A suitable storage medium is necessary to preserve avulsed teeth before replantation. Conditioned medium from placenta-derived mesenchymal stem cells (PMSC-CM) contains a variety of growth factors. The aim of this study was to evaluate the effectiveness of PMSC-CM as a storage medium to maintain the cell viability of avulsed teeth. Material and Methods: Extracted pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of their study showed that HBSS is an optimal storage medium for avulsed tooth when compared with other tested solutions. 5 Ashkenazi et al showed that HBSS was the most effective medium for preserving viability, mitogenicity, and clonogenic capacities of PDL cells for up to 24 hours at 4°C, when compared with culture medium (EM supplemented with 15% foetal calf serum and antibiotic solution containing 100 UI/mL penicillin, 50 μg/mL gentamicin, and 0.3 μg/mL fungizone), EM, milk, ViaSpan, and conditioned medium. 11 Recent studies have evaluated the use of 0.9% isotonic saline, milk, HBSS, and Viaspan as storage media for the preservation of cell viability.…”
Section: Salivamentioning
confidence: 99%
See 2 more Smart Citations
“…The results of their study showed that HBSS is an optimal storage medium for avulsed tooth when compared with other tested solutions. 5 Ashkenazi et al showed that HBSS was the most effective medium for preserving viability, mitogenicity, and clonogenic capacities of PDL cells for up to 24 hours at 4°C, when compared with culture medium (EM supplemented with 15% foetal calf serum and antibiotic solution containing 100 UI/mL penicillin, 50 μg/mL gentamicin, and 0.3 μg/mL fungizone), EM, milk, ViaSpan, and conditioned medium. 11 Recent studies have evaluated the use of 0.9% isotonic saline, milk, HBSS, and Viaspan as storage media for the preservation of cell viability.…”
Section: Salivamentioning
confidence: 99%
“…4 The best treatment protocol is the immediate replantation of the involved tooth at the accident site however; this may not be possible to occur. 5 The ability of a storage/transport medium to support cell viability of the avulsed tooth before treatment can be more important than the extra oral time, for preventing ankylosis and replacement resorption. 6 Various solutions have been investigated as storage media, such as Hank's balanced salt solution (HBSS), milk, aloe vera extract, propolis, coconut water, and egg white.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not observe any acute and long-term treatment-related adverse effects [15]. Ji et al discovered that the conditioned medium from placenta-derived MSCS increased the proliferation and lowered the apoptosis rate in human periodontal ligament stem cells obtained from the extracted premolars [18]. Moreover, placenta-derived MSCs hydrogel appeared as a novel therapeutic option for patients with diabetic foot ulcers.…”
Section: Placenta-derived Mesenchymal Stem Cellsmentioning
confidence: 99%